1996
DOI: 10.1128/jcm.34.4.918-923.1996
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycobacterium tuberculosis by PCR amplification with pan-Mycobacterium primers and hybridization to an M. tuberculosis-specific probe

Abstract: Nucleic acid amplification techniques such as the PCR are very useful in the rapid diagnosis of infections by Mycobacterium tuberculosis. However, recent studies have shown that the accuracy of results can vary widely when tests are performed with nonstandardized reagents. We have developed a PCR assay for the detection of M. tuberculosis that is both rapid and accurate. The assay reagents are standardized and quality controlled. False-positive results due to carryover contamination are prevented by the incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 26 publications
2
39
0
1
Order By: Relevance
“…Thus PCR revealed 76.4% sensitivity and 100% specificity. Similar results were reported by Tevere et al 10 PCR tests of respiratory tract specimens in their study showed 73.1% sensitivity in the AFB smear‐negative group. Tan et al 8 used a different PCR method and reported 100% sensitivity and from 95% to 85% specificity for various specimens such as sputum, bronchoalveolar lavage fluid, pleural fluid, and gastric aspirate.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Thus PCR revealed 76.4% sensitivity and 100% specificity. Similar results were reported by Tevere et al 10 PCR tests of respiratory tract specimens in their study showed 73.1% sensitivity in the AFB smear‐negative group. Tan et al 8 used a different PCR method and reported 100% sensitivity and from 95% to 85% specificity for various specimens such as sputum, bronchoalveolar lavage fluid, pleural fluid, and gastric aspirate.…”
Section: Discussionsupporting
confidence: 91%
“…Tötsch et al 7 performed two different PCR methods with paraffin‐embedded lymph node tissues and reported 100% sensitivity. Tevere 10 and Wobeser et al 11 presented a PCR method with Pan‐ Mycobacterium primer and M tuberculosis ‐specific probe and reported 91.9% sensitivity and 99.8% specificity using 662 respiratory tract specimens. These reports, however, did not present new methods for replacing the established diagnostic tools; rather they are considered preliminary studies for clinical applications, because of their use of surgical biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The universal eubacterial 16S primers (Edwards et al 1989) were used to amplify rDNA from most of the strains tested. Genus-specific 16S primers (Tevere et al 1996) were used to amplify Mycobacterium DNA, and 23S primers (Ludwig et al 1993) were used to amplify rDNA for the screening of the Vibro vulnificus-specific probe. The amplified DNA (1 ml) was spotted onto a nylon membrane (Hybond-N, Amersham International) and fixed by u.v.…”
Section: Preparation Of Membrane Dot Blots Using Pcramplified Dnamentioning
confidence: 99%